Implementasi Metode Multi Attribute Utility Theory (MAUT) Dalam Rekomendasi Jurusan Di Perguruan Tinggi Berbasis Tes Minat RMIB Dan Nilai Rapor (Studi Kasus: Pada Mata Pelajaran Bimbingan Konseling Kelas XI SMAN 3 Kota Bengkulu): Studi Kasus: Pada Mata Pelajaran Bimbingan Konseling Kelas XI SMAN 3 Kota Bengkulu - Azaharah, Diyah Ishita; Coastera, Funny Farady; Andreswari, Desi (UNIB Press, 2024)
This research highlights students' desire to continue their education at university, but they still experience difficulties in choosing what major to take when they go to college. This problem arises because of students' lack of self-understanding regarding interests and potential. The proposed solution is to use a decision support system by combining interest aspects based on the Rothwell Miller Interest Blank (RMIB) test and students' academic abilities based on report card grades. The method applied in this decision support system is Multi Attribute Utility Theory (MAUT) with the system output in the form of recommendation results displayed in ranking form. From the results of functional testing using black box testing, it shows that the system works well with a success value of 100%, while the accuracy measurement reaches a percentage of 73.425% which is in the sufficient category.